Neuronal detection thresholds during vestibular compensation: contributions of response variability and sensory substitution - Jamali, Mohsen; Mitchell, Diana E.; Dale, Alexis; Carriot, Jerome; Sadeghi, Soroush G.; Cullen, Kathleen E. (The Journal of physiology, 2014)
Key points Unilateral vestibular injury impairs our ability to detect motion. However, before this study the neural mechanisms underlying this impairment had not yet been established. We found that the detection thresholds of neurons at the first central stage of vestibular processing (i.e. vestibular nuclei) dramatically increase immediately post‐lesion, and despite some recovery remain elevated even after 1 month, following the trend reported for vestibular patients’ perception. After the lesion, parallel changes in neuronal trial‐to‐trial variability and sensitivity account for consistently elevated thresholds, thus providing a neural correlate for impaired behavioural performance. In a subset of neurons, sensory substitution with extravestibular (i.e. proprioceptive) inputs after the lesion combined with residual vestibular information serves to improve neuronal detection thresholds for head‐on‐body motion. Our results provide a neural correlate for rehabilitation approaches that take advantage of the convergence of proprioceptive and vestibular inputs to improve patient outcomes. The vestibular system is responsible for processing self‐motion, allowing normal subjects to discriminate the direction of rotational movements as slow as 1–2 deg s−1. After unilateral vestibular injury patients’ direction–discrimination thresholds worsen to ∼20 deg s−1, and despite some improvement thresholds remain substantially elevated following compensation. To date, however, the underlying neural mechanisms of this recovery have not been addressed. Here, we recorded from first‐order central neurons in the macaque monkey that provide vestibular information to higher brain areas for self‐motion perception. Immediately following unilateral labyrinthectomy, neuronal detection thresholds increased by more than two‐fold (from 14 to 30 deg s−1). While thresholds showed slight improvement by week 3 (25 deg s−1), they never recovered to control values – a trend mirroring the time course of perceptual thresholds in patients. We further discovered that changes in neuronal response variability paralleled changes in sensitivity for vestibular stimulation during compensation, thereby causing detection thresholds to remain elevated over time. However, we found that in a subset of neurons, the emergence of neck proprioceptive responses combined with residual vestibular modulation during head‐on‐body motion led to better neuronal detection thresholds. Taken together, our results emphasize that increases in response variability to vestibular inputs ultimately constrain neural thresholds and provide evidence that sensory substitution with extravestibular (i.e. proprioceptive) inputs at the first central stage of vestibular processing is a neural substrate for improvements in self‐motion perception following vestibular loss. Thus, our results provide a neural correlate for the patient benefits provided by rehabilitative strategies that take advantage of the convergence of these multisensory cues.